2015
DOI: 10.1111/adb.12292
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking leads to persistent and dose-dependent alterations of brain activity and connectivity in anterior insula and anterior cingulate

Abstract: Although many smokers try to quit smoking, only about 20-25 percent will achieve abstinence despite 6 months or more of gold-standard treatment. This low success rate suggests long-term changes in the brain related to smoking, which remain poorly understood. We compared ex-smokers to both active smokers and non-smokers using functional magnetic resonance imaging (fMRI) to explore persistent modifications in brain activity and network organization. This prospective and consecutive study includes 18 non-smokers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
(53 reference statements)
3
11
0
Order By: Relevance
“…Our findings add to mounting evidence that the insula plays a central role in addictive behavior (Cisler et al, 2013; Goldstein et al, 2009; McHugh et al, 2013; Naqvi et al, 2014; Noel et al, 2013a; Sutherland, McHugh, Pariyadath, & Stein, 2012; Viswanath et al, 2015; Volkow & Baler, 2015; Wisner, Patzelt, Lim, & MacDonald, 2013; Zhang et al, 2015), including cigarette addiction (Addicott et al, 2015; Clewett et al, 2014; Dinur-Klein et al, 2014; Forget, Pushparaj, & Le Foll, 2010; Gaznick, Tranel, McNutt, & Bechara, 2014; Janes et al, 2010; Naqvi et al, 2007; Suner-Soler et al, 2012; Zanchi et al, 2015). The link between the insula and addiction has largely been conceptualized as one that relates to the interoceptive functions commonly attributed to the region.…”
Section: Discussionsupporting
confidence: 75%
“…Our findings add to mounting evidence that the insula plays a central role in addictive behavior (Cisler et al, 2013; Goldstein et al, 2009; McHugh et al, 2013; Naqvi et al, 2014; Noel et al, 2013a; Sutherland, McHugh, Pariyadath, & Stein, 2012; Viswanath et al, 2015; Volkow & Baler, 2015; Wisner, Patzelt, Lim, & MacDonald, 2013; Zhang et al, 2015), including cigarette addiction (Addicott et al, 2015; Clewett et al, 2014; Dinur-Klein et al, 2014; Forget, Pushparaj, & Le Foll, 2010; Gaznick, Tranel, McNutt, & Bechara, 2014; Janes et al, 2010; Naqvi et al, 2007; Suner-Soler et al, 2012; Zanchi et al, 2015). The link between the insula and addiction has largely been conceptualized as one that relates to the interoceptive functions commonly attributed to the region.…”
Section: Discussionsupporting
confidence: 75%
“…In adults, alterations in functional connectivity between the insula and Acc persisted even following prolonged abstinence in adult smokers (Zanchi et al, 2015), and increased functional connectivity between the insula and sensorimotor areas has been associated with favorable outcomes following a quit-attempt (Addicott et al, 2015). Thus, an important future direction will be to employ network-based analyses to identify network-level factors potentially related to smoking-cessation outcomes among youth.…”
Section: Discussionmentioning
confidence: 99%
“…The presented work is an extension of an fMRI dataset previously published by Zanchi et al (14). Details of the study population, fMRI acquisition protocol, task, and fMRI group analyses and results are defined in the abovementioned publication.…”
Section: Methodsmentioning
confidence: 99%
“…For technical details regarding the fMRI parameters, please see Ref. (14). During the functional run, an on–off block-design with two active conditions (smoking and control cue videos) and a neutral condition (cross displayed) developed by Brody et al (15) were shown as in the previous work (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation